Pemanfaatan Sumber Air Bersih Yang Sehat Bagi Masyarakat Di Desa Pucak Kec. Tompobulu, Kab. Maros - Abd. Gafur; Wardiah Hamzah; Nasruddin Syam (Window of Community Dedication Journal, 2022)
Dug wells are one of the sources of clean water used by the people of Pucak Village, Kec. Tompobulu, Kab. Maros Clean water is used for various daily activities. The quality of dug well water that does not meet the requirements will be a source of disease transmission. Problems faced by the community are the absence of clean water source sanitation inspections, interventions to clean water sources that are physically and bacteriologically ineligible and the lack of environmental health education related to clean water sources. The solutions offered are; (1) Inspection of environmental sanitation and quality inspection of clean water sources, (2) Interventions of clean water sources that do not meet health requirements by providing chlorine (Ca (ClO) 2) in well water, (3) Counseling environmental sanitation in relation to public health . Dug well sanitation inspection results show that there is a low risk of 6 (60%), moderate by 2 (20%), high by 1 (10%), very high by 1 (10%) of 10 wells. Physical quality, namely as many as 2 (20%) experienced turbidity, 1 (10%) that smelled and tastes. While the bacteriological quality showed that 6 (60%) of the samples taken did not meet the requirements. Provision of chlorine (Ca (ClO) 2) in community dug wells has improved water quality to become turbid, smelly and tasteless. Public health education provides knowledge and information on water and drinking water treatment. It is recommended that there be guidance and assistance to the community in managing clean water from puskesmas or universities